Replacement hiring and the productivity-wage gap - Sushant Acharya; Shu Lin Wee (Federal Reserve Bank of New York, 2018)
A large and growing share of hires in the United States are replacement hires. This increase coincides with a growing productivity-wage gap. We connect these trends by building a model where firms post long-lived vacancies and engage in on-the-job search for more productive workers. These features improve a firm's bargaining position while raising workers' job insecurity and the wedge between hiring and meeting rates. All three channels lower wages while raising productivity. Quantitatively, increased replacement hiring explains half the increase in the productivity-wage gap. The socially efficient outcome features fewer low-productivity jobs and a 10 percent narrower productivity-wage gap.
Keywords: E32; J63; J64; 330; replacement hiring; productivity-wage gap; unemployment; labor share; efficiency